Understanding Dynamic IS Capabilities for Effective Process Change: A Theoretical Framework and an Empirical Application - Niehaves, Björn; Plattfaut, Ralf; Sarker, Suprateek (International Conference on Information Systems (ICIS 2011), 2011)
Process change remains a hot topic for both business and IT departments in organizations worldwide. In this research-in-progress paper, informed by the Dynamic Capability Theory of the firm, we develop a theoretical framework that contributes to the understanding of IT-enabled business process change, and elements of the dynamic capabilities that contribute to change success. Specifically, our framework differentiates between baseline and ad-hoc capabilities, and structures these capabilities in the three phases of sensing, seizing, and transformation. An application of our framework in a case setting suggests that baseline capabilities are activated and new ad-hoc capabilities built based on project specific features. Indeed, our framework when applied to two contrasting embedded cases within the same organization reveals the nature of dynamic capabilities that potentially affect IS and process change success. Limitations, plans to complete this research, and directions for future research are discussed.